2023
DOI: 10.7150/ijms.85722
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study in Er:YAG Laser Debonding of Lithium Disilicate Crowns: Laser Power Setting vs Crown Thickness

Rifat Gozneli,
Tansu Sendurur,
Esra Silahtar

Abstract: Background: Er:YAG laser is widely used in debonding of all-ceramic veneers nowadays. However, the data about laser parameters in all-ceramic crown removal is limited. The aim of this preliminary study was to determine the most appropriate laser parameters at safe heat transmission values for lithium disilicate crowns in different thicknesses. Methods: Twenty-seven intact premolars were prepared to fabricate lithium disilicate CAD/CAM full-coverage crowns in three different thicknesses: 1, 1.5 mm, and mixed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A high water content is also found in adhesive luting materials, which provide the possibility to debond ceramic restorations. Recent studies have demonstrated a predictable way of retrieving ceramic restorations with Er:YAG or Er,Cr:YSSG lasers [7,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…A high water content is also found in adhesive luting materials, which provide the possibility to debond ceramic restorations. Recent studies have demonstrated a predictable way of retrieving ceramic restorations with Er:YAG or Er,Cr:YSSG lasers [7,[10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%